2018
DOI: 10.1080/07317115.2018.1483992
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Experiences of Driving Cessation and Dementia: A Meta-Synthesis of Qualitative Literature

Abstract: Interventions to support driving cessation for people with dementia should prioritize support for communication, advanced planning, and emotional effects of stopping driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…Driving gives people independence and autonomy, allows them to manage their schedules and needs and socialize and partake in activities that they enjoy [ 21 ]. As such, it is not surprising that driving cessation is associated with negative emotions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Driving gives people independence and autonomy, allows them to manage their schedules and needs and socialize and partake in activities that they enjoy [ 21 ]. As such, it is not surprising that driving cessation is associated with negative emotions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the negative impact of sudden driving cessation on the PLWCDs, caregivers and the relationship between the PLWCD and the physician, it is important that more attention is given to advanced planning and having aging adults and their families prepare for the possibility of driving cessation [ 21 ]. While all caregivers in the study were concerned about PLWCD’s driving, none reported discussions about advanced planning with the PLWCD regarding driving cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the elderly still working in the garden make it a substitute for sports (Kerwin & Hoeber, 2015). Older people who are used to working from a young age will continue to work, some of them say that if they do not work, it makes their bodies feel sick because there is no activity, so they choose to work every day with limited working hours rather than staying at home (Sanford, Naglie, Cameron, Rapoport, & Team, 2020).…”
Section: Want To Be Healthymentioning
confidence: 99%
“…This information was used to make a Buddy Pair match that supported both partners' comfort and ability to interact with one another. We also arranged transportation services on lay participants' behalf, in recognition that transportation difficulties are a significant barrier to people with dementia's participation in activities outside the home (Sanford et al, 2018). While recruitment of lay participants was begun early in the project set-up phase, communication with care partners and people with dementia was maintained until initial tours could be scheduled.…”
Section: Project Set-upmentioning
confidence: 99%